Snake detection system using convolutional neural network / Muhammad Danial Ahmad Tarmizi - Ahmad Tarmizi, Muhammad Danial (2020)
Snake known as most dangerous reptile as it threaten our live and can deal fatal wound for human. Mostly people cannot differentiate between venomous and non-venomous snake because most of non-venomous snake are likely to look like venomous one. This kind of problem can be solved using Artificial Intelligence approach. This paper aims to discuss about the project built for encountering that problems to detect and classify the snakes. Objectives of this project is to design the flow of the system, developed in Window application and test the functionality of the system and reliability for the predictive model. This project uses Convolutional Neural Network algorithms which is one the best algorithms for image processing. The algorithm is built using Tensorflow software. The development of the project is based on Waterfall methodology. Waterfall methodology consists of 6 phases starting from requirement analysis, system design, implementation, testing, deployment and maintenance. The predictive model success in detecting and classifying the snake. The model achieve 96.89 % of accuracy percentage in training set and 96% of accuracy from testing set. This project can be improved by employing in the less consumption hardware like Jetson Nano and using light sensitive camera to improve the image quality while detecting snake.